Rural Elementary Teachers’ Perceptions of Team Teaching - Ulfa Nurhasanah; Utami Dewi (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This research aims to identify teachers’ perceptions of teaching by a team in a rural elementary school. Team teaching is a way to teach in a classroom, the importance of teacher perception is needed to evaluate the strengths and weaknesses of team teaching in an elementary school. The research was used qualitatively design with a descriptive qualitative approach to find problems experienced either individually or in groups. The teachers could review about team teaching that they were through the attached perspective. The research data were obtained through interviews and data collection of material documentation. This research was conducted at rural elementary school of North Sumatera, Indonesia. The findings state that the participants feel comfortable and are helped by team teaching, which shows learning improvement. In addition, it shows the teachers have positive perceptions and teaching experiences with team teaching.